Ovarian Abnormalities in the Staggerer Mutant Mouse - Jean-Marie Guastavino; Salima Boufares; Wim E. Crusio (The Scientific World Journal)
Disturbances in several reproductive functions of the staggerer cerebellar mutant mouse have been observed. In this study, reproductive efficiency of staggerer mice was compared to normal mice by recording the number of pups produced and the number of oocytes occurring. It was found that staggerer mothers produced smaller litters than controls and the number of oocytes produced in their ovaries was reduced by the staggerer mutation. These results indicate a pleiotropic effect on fertility of the Rorasg gene underlying the cerebellar abnormalities of the staggerer mutant.